Das Verhältnis zwischen Hieroglyphen- und Keilschrift-Luwisch: Überlegungen zu den Ursprüngen der anatolischen Hieroglyphenschrift - Breyer, Francis (Altorientalische Forschungen, 2022)
The linguistic differences between Hieroglyphic and Cuneiform Luwian have long been known. However, it is unclear how these should be assessed: How exactly do the two varieties relate to each other? Are they different dialects, just different registers or even different sociolects? Based on the thesis developed recently, according to which the transformation of the Luwian hieroglyphs into a veritable writing system only took place in the context of the late Hittite empire, this article works out that Hieroglyphic Luwian probably is to be considered a functiolect.